Recombinant Amphiphilic Protein Micelles for Drug Delivery - Kim, Wookhyun (2011)
Amphiphilic block polypeptides can self-assemble into a range of nanostructures in solution, including micelles and vesicles. Our group has recently described the capacity of recombinant amphiphilic diblock copolypeptides to form highly stable micelles. In this report, we demonstrate the utility of protein nanoparticles to serve as a vehicle for controlled drug delivery. Drug-loaded micelles were produced by encapsulating dipyridamole as a model hydrophobic drug with anti-inflammatory activity. Murine studies confirmed the capacity of drug loaded protein micelles to limit in vivo recruitment of neutrophils in response to an inflammatory stimulus.